The Role Of Waste Banks In Empowering Plastic Waste Into Economically Valuable Upcycled Handicraft Products : A Study On Waste Bank Wares - Yustina Denik Risyanti; Aurilia Triani Aryaningtyas; Phia Susanti Helyanan (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Sustainable waste management needs serious attention, starting from the concern about people's habits of carelessly disposing of household waste, leading to a dirty and slum environment. If this problem is not addressed, it will become a serious problem that will certainly disrupt people's lives. Facing this situation, the community proactively formed a task force to creatively deal with waste, starting from the utilization of plastic waste that accumulated in the community. This research aims to find out the implementation of plastic waste management with recycling techniques in Bank Sampah Wares, located at Widosari No. 21, RT 03, RW 04 Tegalrejo, Salatiga. This study used a qualitative field research approach with data collection techniques through observation, interviews, and literature studies to explore data and understand waste disposal stakeholders, and their participation to help solve waste problems. The results showed that along with the development of science and technology, the Bank Sampah Wares community implemented a plastic waste processing process using recycling techniques by developing plastic waste into unique and modern handmade products. The handmade product can then be utilized to increase economic value. Besides that, the waste processing site can also be used as a place to foster creativity without requiring high costs by utilizing processed plastic into creative products. This research should be conducted to show that waste bank goods have a strategic role in educating changes in the behavior of residents of the environment in utilizing of waste.